Effects of maturity stages on textural mechanical properties of tomato - INCE, Ahmet; Çevik, Melih Yavuz; Vursavuş, Kubilay Kazım (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: The textural mechanical properties of Jadelo F1 variety tomato were evaluated at three different mature stages (green, pink and red) which were classified according to the colors of the fruit. The compression and the puncture tests were applied on samples. The cycling and relaxation tests showed that indexes of average firmness, energy absorption and deformation ratio were more sensitive parameters to maturity stages than others. The puncture tests indicated that maturity stages were effective on initial and average firmness and skin rupture force. Since the rigidity and the firmness of the fruit reduced, it was more prone to mechanical damage in the process of mature. The initial firmness values obtained fromcompressiontest and average firmness values from puncture tests had the highest correlation with each other which indicates that they can be used as representative parameter for tomato. Moreover, it was found that a*/b* color parameter can be good indicator for evaluating mechanical properties of tomato. Keywords: maturity, textural properties, mechanical properties, color DOI: 10.3965/j.ijabe.20160906.1999 Citation: Ince A, Cevik M Y, Vursavus K K. Effects of maturity stages on textural mechanical properties of tomato. Int J Agric & Biol Eng, 2016; 9(6): 200－206.